Ecosystem importance of roots: A literature review (Research, Society and Development, 2024)
Fine roots are all those with a diameter ≤2 mm. These roots are responsible for a significant portion of the primary productivity of terrestrial ecosystems, being important for providing resources to the soil microbial community and for influencing the cycling of carbon and nutrients. Despite their recognized importance, fine roots are commonly neglected in plant biomass studies. Root biomass studies are generally limited throughout the world, mainly due to the methodological complexity involved in the analytical processes. The objective of this work was to carry out a review of studies on the topic of roots, addressing the development of technologies in the analytical process and the importance of this dynamic biomass component in ecosystem processes related to carbon cycling and soil nutrients. We emphasize here the importance and need for new scientific research that seeks to develop methods of analysis, as well as to estimate the underground primary productivity, especially that of fine roots, so that the processes involved in the cycling of carbon and nutrients are better elucidated.